Facile fabrication of flexible core–shell graphene/conducting polymer microfibers for fibriform supercapacitors. Issue 61 (3rd August 2017) - Meng, Yuning; Jin, Lin; Cai, Bin; Wang, Zhenling
Abstract : We fabricated graphene core conductive polymer (PEDOT) shell fibers (GF@PEDOT). The unique cloth-like structure enabled the graphene fibers excellent electrochemical performance and greatly enhanced the flexibility. Abstract : The doping method is typically applied to highly flexible graphene fibers to improve their gravimetric energy storage capacity and electrical conductivity. However, the applications of these graphene fibers, used for flexible wearable supercapacitors, are limited because of their poor mechanical performance and uniform phase. We fabricated graphene core, conductive polymer (PEDOT) shell fibers (GF@PEDOT) using a hydrothermal strategy combined with an in situ interfacial polymerization method. The unique cloth-like structure granted the graphene fibers excellent electrochemical performance and greatly enhanced their flexibility. Furthermore, the prepared symmetric fiber supercapacitors based on two intertwined GF@PEDOT electrodes with a poly(vinyl alcohol) PVA/H2 SO4 gel electrolyte exhibited high flexibility with a specific capacitance of up to 15.39 mF cm −2 (0.58 mF cm −1 ) at 0.53 mA cm −2 . Combined with the excellent integrated performance, we anticipate this type of core–shell fiber supercapacitors to have promising applications in the next generation of wearable electronics and as highly stretchable supercapacitors.